Systematic QM/MM investigation of factors that affect the cytochrome P450-catalyzed hydrogen abstraction of camphor - Altun, Ahmet (Journal of computational chemistry, 2006)
The hydrogen abstraction reaction of camphor in cytochrome P450(cam) has been investigated in the native enzyme environment by combined quantum mechanical/molecular mechanical (QM/MM) calculations and in the gas phase by density functional calculations. This work has been motivated by contradictory published QM/MM results. In an attempt to pinpoint the origin of these discrepancies, we have systematically studied the factors that may affect the computed barriers, including the QM/MM setup, the optimization procedures, and the choice of QM region, basis set, and protonation states. It is found that the ChemShell and QSite programs used in the published QM/MM calculations yield similar results at given geometries, and that the discrepancies mainly arise from two technical issues (optimization protocols and initial system preparation) that need to be well controlled in QM/MM work. In the course of these systematic investigations, new mechanistic insights have been gained. The crystallographic water 903 placed near the oxo atom of Compound I lowers the hydrogen abstraction barrier by ca. 4 kcal/mol, and thus acts as a catalyst for this reaction. Spin density may appear at the A-propionate side chain of the heme if the carboxylate group is not properly screened, which might be expected to happen during protein dynamics, but not in static equilibrium situations. There is no clear correlation between the computed A-propionate spin density and the hydrogen abstraction barrier, and hence, no support for a previously proposed side-chain mediated transition state stabilization mechanism. Standard QM/MM optimizations yield an A-propionate environment close to the X-ray structure only for protonated Asp297, and not for deprotonated Asp297, but the computed barriers are similar in both cases. An X-ray like A-propionate environment can also be obtained when deprotonated Asp297 is included in the QM region and His355 is singly protonated, but this Compound II-type species with a closed-shell porphyrin ring has a higher hydrogen abstraction barrier and should thus not be mechanistically relevant